Is cannabis treatment for anxiety, mood, and related disorders ready for prime time?. Issue 11 (21st June 2017) - Turna, Jasmine; Patterson, Beth; Van Ameringen, Michael
Abstract: Anxiety and related disorders are the most common mental conditions affecting the North American population. Despite their established efficacy, first‐line antidepressant treatments are associated with significant side effects, leading many afflicted individuals to seek alternative treatments. Cannabis is commonly viewed as a natural alternative for a variety of medical and mental health conditions. Currently, anxiety ranks among the top five medical symptoms for which North Americans report using medical marijuana. However, upon careful review of the extant treatment literature, the anxiolytic effects of cannabis in clinical populations are surprisingly not well‐documented. The effects of cannabis on anxiety and mood symptoms have been examined in healthy populations and in several small studies of synthetic cannabinoid agents but there are currently no studies which have examined the effects of the cannabis plant on anxiety and related disorders. In light of the rapidly shifting landscape regarding the legalization of cannabis for medical and recreational purposes, it is important to highlight the significant disconnect between the scientific literature, public opinion, and related policies. The aim of this article is to provide a comprehensive review of the current cannabis treatment literature, and to identify the potential for cannabis to be used as a therapeutic intervention for anxiety, mood, and related disorders. Searches of five electronic databases were conducted (PubMed, MEDLINE, Web of Science, PsychINFO, and Google Scholar), with the most recent in February 2017. The effects of cannabis on healthy populations and clinical psychiatric samples will be discussed, focusing primarily on anxiety and mood disorders.